2019
DOI: 10.3390/fluids4040205
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Air-Side Heat Transfer and Pressure Drop Characteristics of a New Triangular Finned Microchannel Evaporator with Water Drainage Slits

Abstract: The present study investigated a new microchannel profile design encompassing condensate drainage slits for improved moisture removal with use of triangular shaped plain fins. Heat transfer and pressure drop correlations were developed using computational fluid dynamics (CFD) and defined in terms of Colburn j-factor and Fanning f-factor. The microchannels were square 2.00 × 2.00 mm and placed with 4.50 mm longitudinal tube pitch. The transverse tube pitch and the triangular fin pitch were varied from 9.00 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Kumar et al [2] Parametric optimization 2D CFD: Turbulent flow Rogié et al [3] Parametric optimization 3D CFD: Turbulent flow Alexias et al [4] Continuous adjoint 3D CFD: Laminar flow Olivetti et al [5] Automated DoE Optimization tool and 3D CFD: Turbulent flow Parker et al [6] Smooth and corrugated cylinder Measurements of pressure and velocity Grossberg et al [7] Continuous adjoint Derivation of the adjoint drift flux equations Guerrero et al [8] Cloud-based DSE and DO Optimization tool and 3D CFD: Turbulent flow The paper by Kumar et al [2] is on the topic of small-scale decentralized wind power generation; the authors propose an adaptive hybrid Darrieus turbine (AHDT) to overcome issues experienced by Savonius and Darrieus wind turbines. The AHDT has a Savonius rotor nested inside a Darrieus rotor, where the Savonius rotor can change shape.…”
Section: Paper Methods Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al [2] Parametric optimization 2D CFD: Turbulent flow Rogié et al [3] Parametric optimization 3D CFD: Turbulent flow Alexias et al [4] Continuous adjoint 3D CFD: Laminar flow Olivetti et al [5] Automated DoE Optimization tool and 3D CFD: Turbulent flow Parker et al [6] Smooth and corrugated cylinder Measurements of pressure and velocity Grossberg et al [7] Continuous adjoint Derivation of the adjoint drift flux equations Guerrero et al [8] Cloud-based DSE and DO Optimization tool and 3D CFD: Turbulent flow The paper by Kumar et al [2] is on the topic of small-scale decentralized wind power generation; the authors propose an adaptive hybrid Darrieus turbine (AHDT) to overcome issues experienced by Savonius and Darrieus wind turbines. The AHDT has a Savonius rotor nested inside a Darrieus rotor, where the Savonius rotor can change shape.…”
Section: Paper Methods Toolsmentioning
confidence: 99%
“…Rogié et al [3] compare new microchannel evaporator designs to a baseline finned-tube evaporator; the new designs have drainage slits for improved moisture removal with triangular shaped plain fins. Optimization is carried out by varying the geometry (transverse tube pitch and triangular fin pitch) and the inlet velocity while keeping a constant wall temperature of tube and fin.…”
Section: Paper Methods Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the base temperature of this novel heat sink is lower than the base temperature of a similar circular microchannel heat sink. Rogie et al [ 18 ] designed a new triangular finned microchannel and studied the pressure drop and heat transfer characteristics numerically. The study encompassed the effect of triangular fin pitch and transverse tube pitch in the following ranges of 2.50–10.0 mm and 9.0–21.0 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%